Ryzen 5 (3600, 1600, 1600X) Review - Shaikh, Faizan; Khan, Salman; Ansari, Shaibaz; Shaikh, Shakila; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
In July 7 2019, AMD launched Ryzen 5 3600 processor. This processor was launched to provide better all-round performances like gaming, multitasking, exceptional speed etc. and intention of hitting market by lower price as compare to other processor companies. For example, its competitive processor intel-5 9600k is expensive as compare to ryzen 5 3600.